Ethics for police and society - Sanghaik, Gopal Krishan (2013)
The police is an important organ for the smooth functioning of any society. So it has been entrusted with vast discretionary powers for using police force for maintaining law and order when necessary. Police role has become more significant with increasing crime and problem of law and order. However, the sharp increase in cases of corruption, illicit operation, bribery and extortion has damaged the police image and the distrust against police force is quite alarming. The constant dealing with public requires a deep understanding of human attitude and behaviour which cannot be easily acquired. For laying the foundation of a strong and pervasive culture of integrity, the police force requires trainings based on moral values and ethical awareness. An attempt has been made to suggest effective methods for bringing attitudinal change or inner transformations of police. - Reproduced.
Keywords: Social systems; Ethics; Police